Makna Leksikal Kuliner Tradisional Di Medan, Indonesia–Penang, Malaysia - Ayu Melati Ningsih; Risnawaty Risnawaty; Vera Kristiana; Yayuk Yuliana; Mohd Haizzan Bin Yahaya; Rara Silvany Aulia (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program is a collaboration between Universitas Muslim Nusantara Al-Washliyah and Universiti Sains Malaysia (USM) that explores the cultural and linguistic meanings of traditional cuisines in Medan and Penang. The objective of this community engagement initiative is to preserve culinary heritage through documentation, analysis and comparison of culinary terms, historical roots, and symbolic meaning amidst the challenges of globalization. Using a mixed-method approach-combining field etnography, computational linguistics (AI-based lexical mapping), and semiotic analysis, the team collected data from oral histories, ancient recipes, and digital etnography. The results highlight regional variations related to migration and colonial influences, as well as the documentation of terms such as rendang (Minang) and nasi kandar (Malay-Indian) enriched with etymologies and cultural narratives.